Cover Picture: Exposing the Origins of Irreproducibility in Fluorine NMR Spectroscopy (Angew. Chem. Int. Ed. 30/2018). Issue 30 (22nd May 2018) - Rosenau, Carl Philipp; Jelier, Benson J.; Gossert, Alvar D.; Togni, Antonio
Abstract : One possible barrier to scientific reproducibility is the lack of clear protocols. This is the case for the 19 F NMR referencing of fluorine‐containing compounds. In their Communication onpage 9528 ff., A. D. Gossert, A. Togni, and co‐workers trace back the origins of this problem to poor definitions for 19 F NMR spectroscopy in IUPAC′s unified scale and systematic errors by instrument manufacturers. These difficulties are easily overcome by following a simple procedure, which will serve the community as a modern guideline for the referencing of 19 F NMR spectra.